Peningkatan Efisiensi dan Manajemen Informasi dalam Pelayanan Unit Kesehatan Sekolah (UKS) Berbasis Website - Umar, Adelya; Susanto, Lisdayanti; Syatilla, Fachreiza Rayhan Al; Rauf, Annajmi (PT. Lontara Digitech Indonesia, 2024)
The School Health Unit is an important component in the education system to promote the health and well-being of students. UKS aims to provide comprehensive health services to students, including disease prevention, health monitoring, health counseling, and basic medicine. But there are several obstacles that are often faced in managing data in the UKS, including limited technology infrastructure, lack of training and skills in data management, time constraints, data privacy and security issues and several other obstacles that might occur. For this reason, a website-based information system is needed that can be used easily by all people but still with useful features such as drug stock lists and student visits so as to be more efficient in inputting data. The School Health Unit Information System (SI-UKS) is a technology platform used to manage and organize student health information and support the administrative and operational activities of the School Health Unit. The School Health Unit Information System (SI-UKS) plays an important role in improving the efficiency and management of information in school health services. Through efficient management of student data, good data reporting and analysis, and integrated communication, SI-UKS helps improve the quality of health services and overall student well-being. In designing this website-based Information System using the waterfall method.